WUJUD PENDIDIKAN KARAKTER DALAM NOVEL SASTRA JENDRA HAYUNINGRAT PANGRUWATING DIYU KARYA AGUS SUNYOTO - Fredy Yunanto; Ria Kasanova (KOLONI, 2022)
The educational values that will be discussed in Agus Sunyoto Jendra Hayuningrat Pangruwating Diyu's novel are values that embody the greatness of humanity and are composed in customs, religion, culture, and local wisdom, etc. This study examines 4 (four) values of character education using the literary novel Jendra Hayuningrat Pangruwating Diyu by Agus Sunyoto as a research object. The data collection process consists of identifying, classifying, and qualitatively characterizing the data. The research data is presented as quotations of words, phrases, sentences, clauses, or discourse from the novel Agus Sunyoto Sastra Jendra Hayuningrat Pangruwating Diyu. The data is then identified, classified according to the character education environment, and given an interpretive explanation based on the theory used in this study. This research focuses on character education in the form of: 1) religion, 2) friendly/communicative, 3) scientific spirit, and 4) responsibility. In the literary novel Jendra Hayuningrat Pangruwating diyu, character education takes the form of: 1) faith which is reflected in the behavior of the character Sudrun who always tries to open the secret walls of divinity to get closer to God Almighty. 2) Sociable or communicative, shown by Sudrun's personality in building communication with everyone he meets, including teachers, friends, and people who are his students. 3). The character Sudrun shows his love for science by looking for useful information in books, holy books and ancient fairy tales. 4) Sudrun's character shows responsibility by helping individuals in trouble, caring for foundlings, and rescuing dogs that are near death. Keywords: Character education, novel